A Parametric Study of Coupled Hydromechanical Behaviors Induced by Shallow Water Flow in Shallow Sediments in Deepwater Drilling Based on Numerical Modeling - Xuyang Guo; Yan Jin; Botao Lin (Geofluids)
Shallow water flow is a geohazard encountered in deepwater drilling. It is often characterized by excessive water flow into the wellbore caused by the pressure difference between overpressured sediments and the wellbore, and it usually leads to serious well control problems and may eventually result in the loss of a well. Many research efforts focused on the identification of shallow water flow zones and the associated water flow in the drilled wellbore. Not many studies investigated the coupled hydromechanical behaviors in sediments during the occurrence of shallow water flow, while such behaviors are directly related to uncontrolled flow in the wellbore and solid deformation. Based on a coupled hydraulic-mechanical model and finite element methods, this work investigates the temporal-spatial evolutions of near-well pressure and stress induced by shallow water flow. Hydraulic behaviors in the deepwater shallow sediments are described by saturated fluid flow in porous media while mechanical behaviors in the sediments are depicted by linear elasticity. Finite element methods are used for the numerical solution to the coupled hydraulic-mechanical formulation. The study then conducts a series of parametric studies to quantitatively understand the effects of relevant parameters on pressure, stress, and uncontrolled flow into the wellbore. Results indicate that overpressure has the most significant impact while Young’s modulus has the most limited impact on spatial-temporal pressure/stress evolutions and the uncontrolled water production in the wellbore. Permeability, porosity, water viscosity, and water compressibility all have certain effects on near-well physical characteristics and wellbore water production. In addition, it is noted that pressure drainage and induced stress are more significant when it is closer to the wellbore. This numerical study helps to quantitatively identify the most influential parameters related to shallow water flow and calculates the water mass flow loaded in the wellbore.